High-performance triboelectric nanogenerator via photon-generated carriers for green low-carbon system. (April 2023) - Wang, Fayang; Hou, Liwei; Gao, Lingxiao; Wu, Pengfan; Zhou, Meitong; Chen, Xin; Mu, Xiaojing
Abstract: Enhancing the surface charge density and reducing the output impedance via innovative techniques are essential to accelerate the commercialization of triboelectric nanogenerators (TENGs). However, methods for increasing output performance have numerous limitations, e.g., lacking efficiency and stability. Thus, it is necessary to investigate more practical and efficient strategies to improve the output of TENGs. Here, we leveraged the charge traps generated from photon-carriers through semiconductor materials of TiO2 /g-C3 N4 to boost the TENG output performance. First, the output performance of the TENG can be enhanced by optimizing the dielectric properties of the triboelectric film. Additionally, the photon-generated carriers enable the semiconductor materials to act as charge traps, further enhancing the output performance. Thusly, the peak power of TENG achieves 4.23 mW/cm 2 at the impedance of 3 MΩ, giving over 9.4-fold enhancement for power and a 40 % reduction in impedance compared with pure TENG. What's more, this is the first study to combine the high-performance TENG with the electrostimulation-coupled biosynthesis polyhydroxy butyrate (PHB) system to find a new method to address plastic pollution and environmental protection issues. The biodegradable PHB production increases from 0.752 mg/ml to 0.996 mg/ml under high-current stimulation from TENG. This technology enables rapid and efficient production of bio-based plastic, which has the potential to accelerate carbon neutrality. Graphical Abstract: This work reports a novel strategy based on charge traps from photon-generated carriers in TiO2 /g-C3 N4 composites to further promote the output performance of triboelectric nanogenerator and the first study to combine the high-performance TENG with the electrostimulation-coupled biosynthesis polyhydroxy butyrate (PHB) system to find a new method to address plastic pollution and environmental protection issues. ga1 Highlights: The photon-generated carriers forming the charge traps can enhance the output performance of the TENG. The peak power of TENG achieves 4.23 mW/cm 2 . This is the first study to combine the high-performance TENG with the electrostimulation-coupled biosynthesis PHB system. The biodegradable PHB production increases from 0.752 mg·ml −1 to 0.996 mg·ml −1 .